Service users' and service providers' understandings of addiction and their impact on treatment plans and treatment outcomes. - Garrun, Candice (My University, 2012)
The word addiction is almost immediately associated with notions of drug dependency and alcoholism, and drug addiction is often referred to as a pandemic that affects individuals, families, communities and society at large. Aetiological approaches to understanding and treating addiction have changed dramatically throughout history, and currently the most contemporary approach is that of the disease model which views addiction as an illness rather than as a ‘badness’. While the underpinnings of Narcotics Anonymous’ 12 step philosophy employs non-specific drug language as it views all drugs as having the capacity to become addictive, and while it does not distinguish between the capacity for substances and certain behaviours to become addictive, activities such as overeating, having sex and gambling are yet to be classified as legitimate addictions by the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR). As a result, it appears as if some confusion exists as to whether these behaviours should be classified as impulse control disorders or as genuine addictions due to the various similarities they share in common with substance based disorders. The research conducted explored how people recovering from addiction, as well as how people working with addiction understand addiction and multiple dependency, together with the factors that contribute to relapse and the ability to abstain. Various 12 Step meetings from a variety of 12 Step Fellowships were attended and members were invited to participate in the study. Ultimately seventy eight participants completed a self developed questionnaire which was utilised to assess how people recovering from addiction understood addiction and multiple dependency and the factors that contribute to relapse and the ability to abstain. Quantitative data were analysed via descriptive and inferential statistics. Furthermore twenty participants working with addiction were interviewed with the use of a semi structured interview schedule in order to explore their perceptions around addiction and the factors that contribute to relapse and sobriety. Qualitative data were analysed using thematic content analysis. Results indicated that the majority of recovering addicts and professionals working with addiction understand addiction as a disease. However, discrepancy was apparent with regards to whether or not all recovering addicts have the same disease and subsequently whether all addictions can be treated in the same manner. The above result suggested that there was no standardised, uniform way in which the disease model is understood and interpreted. Factors such as cross addiction, resistance to change and issues relating to the maintenance of change were identified as issues that contribute to relapse, while factors such as aftercare, following the 12 step programme and support were identified as the main aspects that contribute to sobriety. No statistical significance was noted between participants who had relapsed as opposed to those who had not for variables of sensation seeking, impulsivity and perceived stress (which may have been as a result of small sample size). Deeper understanding of the disease model together with broader application of it, and a focus on appropriate training and more comprehensive assessment could perhaps see a reduction in high rates of relapse and recidivism more commonly known as the ‘revolving door syndrome’.
Keywords: Addiction; 12 steps; Disease model; Substance based addiction; Multiple dependency; Cross addiction; Relapse; Abstinence; Revolving door syndrome; Behaviour based addiction